THE DETERMINANTS OF TAX COMPLIANCE: LOVING OR FEARING - Mayapada, Arung Gihna; Muliati, Muliati; Tampang, Tampang; Djaniba, Erlina (Widya Mandala Surabaya Catholic University, 2021)
Research Purposes. This study aims to analyze the internal and external determinants of tax compliance. The internal determinant in this study is a feeling of love for the motherland which is manifested through the soul of patriotism and nationalism. Meanwhile, external determinants that cause fear of taxpayers are tax sanctions.Research Methods. The type of this research is quantitative research. The research data was obtained by distributing questionnaires to all individual taxpayers registered at the Tax Office of Palu. The sampling method is used a random sampling technique so that the total sample of this study is 94 respondents. The data analysis method used in this study is multiple linear regression analysis.Research Results and Findings. The results show that the spirit of patriotism does not affect taxpayers to comply with tax regulations. Meanwhile, nationalism has a significant effect on tax compliance. Meanwhile, tax sanctions have proven unable to increase tax compliance. The findings of this study have implications for the economic theory of tax compliance and social identity theory.